Implementasi Susastra Hindu dalam Strategi Pendidikan Agama untuk Membangun Karakter dan Moralitas Siswa di SMKN 1 Klungkung (Haridracarya: Journal of Hindu Religious Education, 2023)
This research highlights the importance of implementing Hindu literature in religious education strategies at SMKN 1 Klungkung to develop students' character and morality. Using a descriptive qualitative approach through literature review, this study examines the values found in Hindu literature such as the Bhagavad Gita, Sarasamuscaya, and Canakya Nitisastra, which are relevant for shaping students' morality. Values such as dharma (truth), ahimsa (non-violence), and satya (honesty) are crucial in building strong and moral character. The implementation of this strategy involves integrating the values of Hindu literature into the religious education curriculum, using innovative teaching methods such as storytelling and drama to help students understand and internalize moral values. Additionally, the involvement of teachers and parents is important in shaping students' character, where teachers serve as role models and parents provide support at home. The results of the study show that religious education that integrates Hindu literature not only strengthens students' understanding of religious teachings theoretically but also helps them apply these teachings in daily life, shaping individuals with high moral integrity. Thus, the implementation of Hindu literature in religious education becomes key to shaping a moral and character-driven young generation that is ready to face the challenges of globalization, while also strengthening cultural identity and traditional values that are often marginalized in modern society. Through this approach, schools can create a learning environment that supports the intellectual, moral, and spiritual development of students, shaping them into responsible citizens who contribute positively to society
Keywords: Hindu Literature; Religious Education; Character; Morality